2014
DOI: 10.1364/oe.22.018807
|View full text |Cite
|
Sign up to set email alerts
|

Highly reflective Bragg gratings in slightly etched step-index polymer optical fiber

Abstract: During the past few years, a strong progress has been made in the photo-writing of fiber Bragg gratings (FBGs) in polymer optical fibers (POFs), animated by the constant wish to enhance the grating reflectivity and improve the sensing performances. In this paper, we report the photo-inscription of highly reflective gratings in step-index POFs, obtained thanks to a slight etching of the cladding. We demonstrate that a cladding diameter decrease of ~12% is an ideal trade-off to produce highly reflective gratings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 30 publications
1
44
0
Order By: Relevance
“…Though many researchers have fabricated sensors based on etched silica and polymer fibers, the impact of etching on its sensing capabilities are not investigated yet [5], [11]. Hu et al [12] reported that a cladding diameter decrease of 12% via etching is an ideal trade-off to produce highly reflective gratings by using Trans-4-stilbenemethanol-doped photosensitive step-index poly (methyl methacrylate) (PMMA) POFs. However the change in material properties due to etching and its influence on the sensors are still unknown.…”
Section: Etching Effect On Polymer Optical Fiber Propertiesmentioning
confidence: 99%
“…Though many researchers have fabricated sensors based on etched silica and polymer fibers, the impact of etching on its sensing capabilities are not investigated yet [5], [11]. Hu et al [12] reported that a cladding diameter decrease of 12% via etching is an ideal trade-off to produce highly reflective gratings by using Trans-4-stilbenemethanol-doped photosensitive step-index poly (methyl methacrylate) (PMMA) POFs. However the change in material properties due to etching and its influence on the sensors are still unknown.…”
Section: Etching Effect On Polymer Optical Fiber Propertiesmentioning
confidence: 99%
“…With this laser, the writing time in POFs was ranging from few to hundreds of minutes depending on the polymer material the fibers were made from, the inscription power, the structure of the fibers, and so on [8,19,21,22]. These inscription times can be significantly reduced by doping the fiber, which can be made with trans-4-stilbenemethanol (TS) that can also increase the grating reflectivity [28,29]. Benzyl dimethyl ketal (BDK) PMMA POFs also demonstrated inscription times as short as 4 minutes with a HeCd CW laser [30] and to 40 seconds with a femtosecond laser [31] or even to 1 pulse using a KrF pulsed laser [4].…”
Section: Introductionmentioning
confidence: 99%
“…There are also some theoretical studies about SPR excitation with microstructured POFs [4,5]. In the meantime, the manufacturing of fiberBragg gratings (FBGs) in POFs has matured to such a degree that it is now possible to obtain deep refractive-index modulations with good uniformity and repeatability [6][7][8][9][10].…”
mentioning
confidence: 99%